2008
DOI: 10.1177/1533317508325095
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam: A Practical Option for Seizure Management in Elderly Patients With Cognitive Impairment

Abstract: Cognitive impairment and seizures are common in our aging population. Anticonvulsant treatment is problematic due to sedation, cognitive slowing, and behavioral changes. Levetiracetam has favorable pharmacokinetics, good efficacy in elderly individuals, a favorable side effect profile, and lacks major drug interactions. We conducted a prospective, uncontrolled, phase 4, open label, 12-week study of levetiracetam to better profile its efficacy, safety, and impact on cognitive/behavioral status in 24 cognitively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…In AD, studies are available on levetiracetam (LEV), lamotrigine (LTG), gabapentin, carbamazepine, valproic acid, phenytoin, and phenobarbital (Horváth et al, 2016;Vossel et al, 2017). Only LEV and LTG reached excellent efficacy (60-70% reduction in the number of seizures in a 1-year follow-up) and tolerability without cognitive side effects (Belcastro et al, 2007;Cumbo and Ligori, 2010;Lippa et al, 2010). Notably, treatment with LEV resulted in marginally increased cognitive scores (MMSE and ADAS-Cog), and application of LTG was associated with significantly improved mood (Cumbo and Ligori, 2010), but the study was not placebo controlled.…”
Section: Therapeutic Aspects Current Findings and Recommendationsmentioning
confidence: 99%
“…In AD, studies are available on levetiracetam (LEV), lamotrigine (LTG), gabapentin, carbamazepine, valproic acid, phenytoin, and phenobarbital (Horváth et al, 2016;Vossel et al, 2017). Only LEV and LTG reached excellent efficacy (60-70% reduction in the number of seizures in a 1-year follow-up) and tolerability without cognitive side effects (Belcastro et al, 2007;Cumbo and Ligori, 2010;Lippa et al, 2010). Notably, treatment with LEV resulted in marginally increased cognitive scores (MMSE and ADAS-Cog), and application of LTG was associated with significantly improved mood (Cumbo and Ligori, 2010), but the study was not placebo controlled.…”
Section: Therapeutic Aspects Current Findings and Recommendationsmentioning
confidence: 99%
“…A blinded study showed recent memory improved most in patients with poor baseline scores [Huang et al 2008]. In addition, at least two studies have reported improvements on the Mini-Mental State Examination with use [Lippa et al 2010;Wu et al 2009], one of these in elderly patients with cognitive impairment [Lippa et al 2010].…”
Section: Levetiracetammentioning
confidence: 99%
“… 1 Levetiracetam (LEV) has proven to be a good option because it presents linear pharmacokinetics, renal excretion (therefore less drug interaction), is broad spectrum (used in generalized and focal seizures), while some studies have also shown some degree of benefit in cognitive function. 28 - 30 However it is important to mention that the main concerns with LEV are behavioral side effects, most commonly depression, with a prevalence of approximately 7%. 1 …”
Section: Resultsmentioning
confidence: 99%